Changes in Soil Organic Carbon and Enzyme Activity After Land Use Change in Northeast China - Yang Wang; Te Shan; Peng Zhang; Ming Li (Agronomy)
In Northeast China, the establishment of irrigated paddy fields manifests on soil characterized as upland soils. However, the implications of soil conversion from upland soil to paddy soil for soil aggregates, soil organic carbon (SOC), and enzyme activity within soil aggregates remain poorly understood. Exploring the repercussions of soil conversion on SOC is paramount in delineating enhanced strategies for ameliorating soil structure and bolstering organic carbon sequestration within terrestrial ecosystems. Therefore, this study aimed to quantify the impact of land use modifications on SOC content and enzyme activity within soil aggregates. In this study, paddy (rice field) and upland (maize field) plots were selected from Mollisols in Northeast China, which is characterized by akin soil type, level topography, and climatic conditions. The results indicated that microaggregates represented the predominant fraction in both land use types, ranging from 36.96% to 48.99%, with a notably higher proportion in paddy soil compared to upland soil. After 40 years of rice cultivation, a significant decrease of 9.90% and 2.97% was observed in mean weight diameter and geometric mean diameter, respectively. In paddy soils, the SOC content in aggregates of varying sizes had the following order: macroaggregates (26.41 g kg−1) < microaggregates (21.91 g kg−1) < silt + clay (15.55 g kg−1) fractions. Similarly, in upland soil, the highest SOC content was found in macroaggregates, with the following sequence: macroaggregates (21.67 g kg−1) < microaggregates (17.44 g kg−1) < silt + clay (15.03 g kg−1) fractions. β-glucosidase (BG) displayed the highest enzyme activities, with average values of 95.99 nmol h−1 g−1 in paddy soil and 85.34 nmol h−1 g−1 in upland soil. Macroaggregate fractions exhibited the highest BG activity in both soil types (paddy: 112.49 nmol h−1 g−1, upland: 96.71 nmol h−1 g−1). In conclusion, the conversion from upland fields to paddy fields changes the occurrence mechanism of SOC in the aggregate, which is an important way of sustainable C sequestration in cropland ecosystems.